Performance comparison of diesel and Auto-LPG jeepney. - Mercado, Jose Gabriel E. (UPCOE NEC Technical Bulletin)
Jeepneys are the most common mode of public transportation in the Philippines but most jeepneys in the country are powered by diesel engines that produces harmful emissions to the environment. The Philippine government now promotes the use of alternative fuels in public transportation to lessen the harmful emissions and to make us less dependent on fossil fuels. This study shows that Auto-LPG powered jeepney is a good alternative to the diesel-powered jeepney in most routes in the Philippines because with respect to Fuel Economy the Auto-LPG powered jeepney is 22.26% better than the Diesel Jeepney.